Effects of Roasting Temperature and Time on the Chemical Composition of Argan Oil - Rahma Belcadi-Haloui; Abderrahmane Zekhnini; Yassine El-Alem; Abdelhakim Hatimi (International Journal of Food Science)
This work aimed at assessing the effects of roasting temperature and duration on chemical composition of argan oil. Thus, argan oils extracted from almonds roasted at different temperatures (75-175°C) and times (10-30 min) were analyzed and compared to a control. The physicochemical parameters (acidity, peroxide value, and absorbance at 232, 270 nm) increased slightly and the fatty acid composition did not show significant variation, regardless of roasting temperature and duration. The browning index increased significantly for temperatures greater than or equal to 100°C. The tocopherols content significantly decreased with roasting temperature and time (from 977.9 to 305.2 mg/kg after roasting at 175°C for 10 min). However, fluctuations are noted as a function of temperature. The phospholipids content increased with roasting temperature and time (from 0.198 % to 1.370 % after roasting at 175°C for 30 min). The decrease in the tocopherols content would be due to their thermolability. The increase in phospholipids and tocopherols content could be explained by better extractability. The results obtained make it possible to conclude that a roasting at 125-150°C / 10 min would allow the development of the organoleptic properties of the oil, notably its hazelnut flavour, without compromising its oxidative stability.